2022
DOI: 10.1097/as9.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Diagnosis and Management of Chyle Leak Following Esophagectomy for Cancers

Abstract: Objective: This Delphi exercise aimed to gather consensus surrounding risk factors, diagnosis, and management of chyle leaks after esophagectomy and to develop recommendations for clinical practice. Background: Chyle leaks following esophagectomy for malignancy are uncommon. Although they are associated with increased morbidity and mortality, diagnosis and management of these patients remain controversial and a challenge globally. Methods: This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Two other studies reported a lower incidence of chylorrhagia after esophagectomy in patients with high body mass index [ 7 , 8 ]. According to the 2022 international consensus statement [ 9 ], there is still a lack of standard management and treatment options for these cases [ 10 ]. This study used a systematic review to search the literature databases for original studies investigating the occurrence of chylous leakage after esophagectomy for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies reported a lower incidence of chylorrhagia after esophagectomy in patients with high body mass index [ 7 , 8 ]. According to the 2022 international consensus statement [ 9 ], there is still a lack of standard management and treatment options for these cases [ 10 ]. This study used a systematic review to search the literature databases for original studies investigating the occurrence of chylous leakage after esophagectomy for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%